Coping with stressors in late adolescence/young adulthood: a salutogenic perspective - Ann-Marie K Hutchinson; Anita D Stuart; Hester G Pretorius (AOSIS, 2007)
Literature indicates that globally young people are increasingly experiencing life as hopeless and meaningless. Opsomming Literatuur dui aan dat alhoemeer jong volwassenes hulle lewens as leeg en betekenloos ervaar. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.